(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
India stands among one of the fastest developing economy among the category of developing nations, and to sustain this pace of development the role of Rural Development cannot be overlooked, and one of the core ingredient of rural development is “Micro Finance” as no economy can grow without the active role of financing, and due to lack of formal sources of financing in rural areas, the role of ‘Micro Finance” has increased by leaps and bounds in the last decade. In light of this the present paper deals with the emergence, mechanism, role, and intensity of microfinance in context to rural areas, and the role played by SHG’s and MFI’s in this context.